2014
DOI: 10.1186/1757-7241-22-16
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 as inflammatory marker referring to multiple organ dysfunction syndrome in severely injured children

Abstract: Background: Despite the suggestion that the inflammatory response in traumatized children is functionally unique, prognostic markers predicting pediatric multiple organ failure are lacking. We intended to verify whether Interleukin-6 (IL-6) displays a pivotal role in pediatric trauma similar to adults. Methods: Traumatized children less than 18 years of age with an Injury Severity Score >9 points and consecutive admission to the hospital's pediatric intensive care unit were included. Organ function was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…IL-6 is a prognostic marker for trauma outcome and development of multiple organ failure. Increased posttraumatic IL-6 levels have been associated with unfavorable outcome [ 20 , 21 ]. In this regard, Pape et al indicated that IL-6 levels >800 pg/ml were associated with increased organ failure in multiple injured patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is a prognostic marker for trauma outcome and development of multiple organ failure. Increased posttraumatic IL-6 levels have been associated with unfavorable outcome [ 20 , 21 ]. In this regard, Pape et al indicated that IL-6 levels >800 pg/ml were associated with increased organ failure in multiple injured patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical point of view, the critically ill polytrauma patient is characterized by a series of primary traumatic injuries, as well as by a multitude of trauma-associated secondary injuries such as hemorrhagic shock, tissue hypoxia, generalized inflammation, oxidative stress, and infections. All of these subsequently lead to a multiple organ dysfunction syndrome (MODS) and to a significant increase in mortality rates [7,[31][32][33][34].…”
Section: Molecular and Pathophysiological Aspects Of Metabolismmentioning
confidence: 99%
“…Pediatric major trauma patients are also at risk for MODS; data suggest that MODS occurs in as many as 12% of children admitted to a pediatric intensive care unit with an injury severity score greater than nine (56). Much of that morbidity would appear to be associated with traumatic brain injury as the incidence of MODS in pediatric trauma patients decreases substantially when TBI patients are excluded from analysis (57).…”
Section: Traumamentioning
confidence: 99%
“…The pathogenesis of MODS associated with pediatric trauma is just beginning to be elucidated, but would appear to emanate from a variety of potential causes including inflammation, immune dysfunction, endothelial injury, secondary infection and hemorrhage. Data suggest that IL-6 levels are elevated in critically injured children with some data suggesting an association between these levels and the occurrence of MODS (56, 58). Additionally, immune paralysis has also been reported in critically injured pediatric trauma patients using ex vivo lipopolysaccharide-induced tumor necrosis factor alpha production capacity assessments (58).…”
Section: Traumamentioning
confidence: 99%